Pulmonary Toxicity and the Pathophysiology of Electronic Cigarette, or Vaping Product, Use Associated Lung Injury - Chand, Hitendra S.; Muthumalage, Thivanka; Maziak, Wasim; Rahman, Irfan (Frontiers in Pharmacology, 2020)
New emerging tobacco products, especially electronic cigarettes (E-Cig) or electronic nicotine delivery systems (ENDS), have gained a huge popularity, particularly in younger populations. The lack of sufficient evidence-based health effect studies has promoted widespread use/abuse with the assumption that E-Cig or ENDS and/or vaping products are safer and less toxic than conventional tobacco smoking. However, the recent escalation in acute lung injuries and their associated fatalities among ENDS or vaping product users has now brought attention to this silent epidemic via investigation into the constituents of ENDS/vaping products and their toxic effects on pulmonary health. Accordingly, CDC has declared an “outbreak” of the e-cigarette or vaping product use associated lung injury (EVALI). EVALI is characterized by sterile exogenous pneumonitis like reaction with substantial involvement of innate immune mechanisms. Vitamin-E acetate (VEA) is found in counterfeit cartridges and bronchoalveolar lavage fluid of EVALI patients. Other reports implicated the presence of aromatic/volatile hydrocarbons and oils consisting of medium-chain triglycerides (MCT oil), including terpenes and mineral oil in tetrahydrocannabinol (THC) containing counterfeit vaping products. These compounds are involved in oxidative stress and inflammatory responses in the lung. Here, we provide the perspectives on the recent case reports on EVALI, etiology, and discuss pulmonary toxicity as well as the mechanisms underlying EVALI susceptibility and lung pathophysiology.